Alkyl Carbazates for Electrochemical Deoxygenative Functionalization of Heteroarenes. Issue 27 (30th April 2020) - Gao, Yongyuan; Wu, Zhengguang; Yu, Lei; Wang, Yi; Pan, Yi
Abstract: The C−O bond cleavage for activation of alcohols is synthetically useful and practically challenging. This work describes carbazate as a new type of electrochemically activated alkylating agent derived from ubiquitous alcohols for direct functionalization of heteroarenes under mild electrolytic conditions. The simple undivided cell at low oxidative potentials with carbon/platinum electrode set‐ups offers excellent substrate tolerance, affording a variety of primary, secondary and tertiary alkyl‐decorated heterocycles in good chemical yields. Furthermore, the mechanism for this electrochemical deoxyalkylation reaction has been investigated. Abstract : Carbazates are introduced as a new type of electrochemically activated alkylating agent for direct functionalization of heteroarenes under mild cell conditions.